Contemporary Bali Contested Space and Governance - Wardana, Agung; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book offers a comprehensive examination of spatial and environmental governance in contemporary Bali. In the era of decentralisation, Bali's eight district governments and one municipality acquired a strong sense of authority to extract revenues from within their territorial borders while disregarding the impacts beyond them which has exacerbated environmental, cultural and institutional issues. These issues are addressed through reorganising space. In reality, however, such re-organisation has predominantly been in order to provide space for tourism investments and market expansion. The outcomes of reorganising space are in fact shaped by the dynamics of power that interface with increasingly complex legal and institutional structures. These complex structures provide more arenas for vested interests to manoeuvre, but at the same time provide different forms of legitimacy for local forces to challenge the dominant process. The book demonstrates the mechanisms through which socialactors mobilise legal-institutional arrangements to advance their interests.
Chapter 1 Introduction -- Chapter 2 The Politics of Development in Bali -- Chapter 3 Crisis and Reorganisation of Space -- Chapter 4 Contesting Sacred Boundaries of Uluwatu -- Chapter 5 The Making of World Heritage Landscape -- Chapter 6 Reclaiming the Common of Benoa Bay -- Chapter 7 Rescaling Space and Resistance -- Chapter 8 Conclusion.
Keywords: Human geography; Political sociology; Economic development; Asia -- Politics and government; Environmental Law; Human Geography; Political Sociology; Development Studies; Asian Politics; Environmental Law